160k views
1 vote
M2 + m -2=0
Show work please
Solve in quadratic form

User Zochamx
by
5.3k points

1 Answer

1 vote

Answer:

Explanation:

The quadratic formula is a bit tedious for this since it factors so easily, but if that's what you're told to do, you should probably do it!

The quadratic formula is as follows:


x=(-b+/-√(b^2-4ac) )/(2a)

For us, a = 1, b = 1, c = -2:


x=(-1+/-√(1^2-4(1)(-2)) )/(2(1)) which simplifies to


x=(-1+/-√(1+8) )/(2) which simplifies a bit more to


x=(-1+/-√(9) )/(2) which gives you the 2 solutions of


x=(-1+3)/(2)=1 and


x=(-1-3)/(2)=-2

User Zeucxb
by
5.5k points